EVALUASI PROGRAM PEMBINAAN PRESTASI CABANG OLAHRAGA BOLA VOLI PANTAI DI NTB - Muhammad Ridwan Lubis; Baiq Satrianingsih; Johan Irmansyah (Jurnal Ilmiah Mandala Education (JIME), 2017)
This study was aimed to evaluate the implementation of development program of beach volleyball sport in the West Nusa Tenggara by using the CIPP evaluation model (Contexs, Input, Process, Product). This study was an evaluation. The data were collected through observation, interviews, questionnaires, and documentation. Data analysis techniques used in this research was descriptive quantitative and qualitative analysis. The results show that the overall results of the evaluation of the achievements of sports coaching program of beach volleyball in the NTB are still not good. At the evaluation of the coaching program achievement in the NTB, in terms of contexs it has been running well. In terms of the input is still not good. In terms of process it is still very poor. In terms of product in general the achievement has been good, it can be seen from the accomplishment documentation ever achieved by athletes of NTB